Heritage languages a language contact approach - Aalberse, Suzanne (Studies in bilingualism ;, 2019)
"Heritage languages, such as the Turkish varieties spoken in Berlin or the Spanish used in Los Angeles, are non-dominant languages, often with little prestige. Their speakers also speak the dominant language of the country they live in. Often heritage languages undergo changes due to their special status. They have received a lot of scholarly attention and provide a link between academic concerns and educational issues. This book takes a language contact perspective: we consider heritage languages from the perspective of their history, their structural properties, and their interaction with other surrounding languages"--